Role of Vitamin D3 in Regulation of T Helper Cell 17 and Regulatory T-Cell Balance in Rats With Immunoglobulin A Nephropathy (Iranian Journal of Kidney Diseases, 2014)
Introduction. Dysregulation of CD4+ T cell subsets participates in the pathogenesis of immunoglobulin A nephropathy (IgAN).  Vitamin D has immunomodulatory functions. This study aims to investigate the regulatory effect of vitamin D3 on T helper- regulatory T (Th17-Treg) cells balance in rats with IgAN. Materials and Methods. Sprague-Dawley rats were randomly assigned to a normal group (n = 6), an IgAN model group (n = 5), a prednisone treatment IgAN group (n = 6), a 1,25-dihydroxyvitamin D3 IgAN group (n = 6), and prednisone plus 1,25-dihydroxyvitamin D3 treatment group (n = 6). At week 12, the 24-hour urine protein excretion and erythrocyte count and renal pathological changes were determined, and serum interleukin-17 and Treg cell levels were measured in blood. Results. The urine protein content and the number of erythrocytes were lower in the vitamin D group than in the model group (P < .01), but higher than in the prednisone groups (P